Layout method and numerical simulation study of reduced-hole blasting in large-section tunnels - Liu, Xia; Tao, Tiejun; Tian, Xingchao; Lou, Qianxing; Xie, Caijin (Frontiers in Earth Science, 2022)
Traditional tunnel-drilling and blasting parameter design is based on the small-section roadway and involves many boreholes and conditions that require slow operation progress, and thus cannot meet the rapid operation requirements of a large-span tunnel. Taking Baizhushan Tunnel as the engineering background, this paper puts forward a theoretical basis for a hole-reducing layout method for large-section tunnel blasting. This parameters of the rock statics and dynamics were obtained through core-drilling sampling in the field and the development of static and dynamic tests. LS-DYNA software was used to establish the numerical model of large-span tunnel blasting. The method was verified through the three aspects of the cavity effect, effective stress, and surrounding rock damage, and was implemented in the field application. The results showed the following: the scheme for reducing-hole numbers used 26 fewer blast holes per cycle footage, and saved 0.7 h of drilling time; the average effective stress of the retained rock was 0.6 times that of the original blasting scheme, which reduced the damage to the remaining rock; the maximum over-excavation thickness control was within 50 cm, which reduced over-break; In the field test, the utilization rate of cutting holes was 81.9%, the utilization rate of other blasting holes was 91.2%, the unit consumption of explosives was 0.72 kg/m3, the average over-excavation thickness control was within 20 cm, and the smooth blasting effect was superior.